Impurity removal method for high-pressure hydrolysate of iron-containing solid waste cobalt-iron alloy pickle liquor

By treating the high-pressure hydrolysate of cobalt ferroalloy acid in iron-containing solid waste with ferric chloride solution, aqueous ammonia solution and sodium hydroxide solution, hydrothermal reaction and complexation to remove impurities, the problem of smelting slag turning into hazardous waste and producing a large amount of industrial gypsum in the existing technology is solved, and the purification and resource utilization of iron-containing solid waste is realized.

CN119553085APending Publication Date: 2025-03-04SHANGHAI JIAOTONG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411726630.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When the prior art extracts valuable elements from non-ferrous smelt slags by wet method, it faces the risk of smelting slags from solid waste to hazardous waste, and the problem of the large amount of industrial gypsum generated after lime neutralization, making it difficult to achieve resource utilization.

Method used

By treating the high-pressure hydrolysate of the iron-containing solid waste cobalt ferroalloy acid inlet with ferric chloride solution, aqueous ammonia solution and sodium hydroxide solution, hydrothermal reaction and complexation can remove impurity elements such as lead, zinc and calcium, and reduce the impurity content of the iron-containing solid waste.

Benefits of technology

The purification and resource utilization of iron-containing solid waste is realized, and the content of impurities is reduced. The obtained iron-containing materials are suitable as iron source for battery-grade iron phosphate, avoiding the production of industrial gypsum after lime neutralization, with low cost and simple process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553085A_ABST
    Figure CN119553085A_ABST
Patent Text Reader

Abstract

The invention relates to an impurity removal method for a high-pressure hydrolysate of an iron-containing solid waste cobalt-iron alloy pickle liquor, which comprises the following steps: S1, adding the high-pressure hydrolysate of the iron-containing solid waste cobalt-iron alloy pickle liquor into a ferric trichloride solution, mixing, stirring, centrifuging and cleaning; s2, adding the cleaned solid obtained in the step S1 into an ammonia water solution, mixing, stirring and centrifuging; and S3, transferring solids obtained by centrifugation in S2 into a sodium hydroxide solution, fully stirring, carrying out a hydrothermal reaction, centrifuging the obtained product, washing with water, and drying to obtain an iron-containing material product, thereby completing impurity removal treatment. Compared with the prior art, the method disclosed by the invention has the advantages of simple process route, low purification cost, easiness in large-scale production and the like, and has important significance on resource utilization of iron-containing solid wastes in China.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of iron-containing solid waste, and relates to a method for removing impurities from a high-pressure hydrolysis product of an iron-containing solid waste cobalt-iron alloy acid leaching solution. Background Art

[0002] The nonferrous smelting process produces a large amount of smelting slag. The output of these smelting slags is huge, and it is the third largest industrial solid waste after tailings and coal gangue. According to statistics, the lead smelting system will emit 0.71 tons of smelting slag for every ton of metallic lead produced, the zinc smelting system will emit 0.96 tons of smelting slag for every ton of metallic zinc produced, and the copper smelting system will emit 2-3 tons of smelting slag for every ton of metallic copper produced. Red mud is a polluting waste slag discharged after extracting alumina from bauxite, and 0.8-1.5 tons of waste slag will be emitted for every ton of alumina produced. Nonferrous smelting slag is a kind of industrial solid waste, but nonferrous smelting slag usually contains 30-40% iron, which is an important secondary resource and urgently needs to be utilized.

[0003] Cobalt-containing slag from copper smelting is a typical industrial solid waste. The iron content in the smelting slag is high, while the cobalt content is low. However, cobalt is a high value-added product, and its market price can reach about 200,000 yuan / ton. Therefore, after the cobalt element is extracted from the cobalt-containing slag from copper smelting by acid leaching, the remaining solution is an acidic ferrous sulfate solution with a high iron content, and the divalent iron ions are easily hydrolyzed. After the acid leaching solution is treated with high-pressure hydrolysis, an iron-containing solid waste with a high iron content can be obtained, which is also called the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution. In recent years, the rapid development of new energy vehicles has led to a sharp increase in the demand for lithium iron phosphate, a positive electrode material for lithium-ion batteries, and the supply of raw iron sources for the preparation of lithium iron phosphate has become an important issue that cannot be ignored. The high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution has a high iron content and is a potential candidate as an iron source for lithium iron phosphate positive electrode materials.

[0004] Pyrometallurgical extraction of valuable elements from non-ferrous smelting slag is a common method. For example, many zinc smelting companies use pyrometallurgical extraction of valuable elements zinc from zinc smelting slag. The advantages of using pyrometallurgical extraction of zinc from smelting slag are simple process and easy industrialization. The treated smelting slag is still solid waste and does not involve secondary treatment. The disadvantage is that the pyrometallurgical treatment of smelting slag consumes a lot of energy, while the zinc content in the smelting slag is low. The value of the extracted zinc usually cannot offset the high-temperature energy consumption problem of the pyrometallurgical treatment. In addition, the amount of solid waste after zinc extraction from smelting slag does not change much. It is difficult to reduce the amount of smelting slag by pyrometallurgical treatment. Wet extraction of valuable elements from smelting slag is a relatively effective method. For example, Bayannaoer Zijin Nonferrous Metals Co., Ltd. (CN201510084538.X) extracts and separates valuable metals from high-leaching slag produced by wet zinc smelting. The patented method first converts the valuable metal elements released by the decomposition of ferroaluminate and silicate in the high-leaching slag into an easily floatable form under strong alkaline conditions. Then, through flotation technology, silver concentrate, iron concentrate and lead concentrate are selected respectively. Beijing Qingxin Environmental Technology Co., Ltd. (CN201811306258.9) adopts a wet process (alkali leaching, purification, carbon separation, acid leaching, copper precipitation, secondary alkali leaching, arsenic precipitation, acid dissolution, sulfidation, iron precipitation, zinc precipitation, carbonate lead precipitation, nitric acid dissolution, sulfuric acid lead precipitation and third alkali leaching) to comprehensively recover the valuable metal elements copper, lead and zinc from a zinc smelting waste slag, and the arsenic element can be harmlessly treated. The wet technology mainly treats the smelting slag by acid leaching, so that the valuable metal elements in the smelting slag enter the solution, and then separates them according to the differences in the physical / chemical properties of the metal elements.

[0005] The wet process usually has a high separation efficiency for valuable elements and is currently widely used, but the problems are: (1) If the content of valuable elements in the smelting slag is low, the amount of smelting slag acid leaching liquid will become very large after acid leaching treatment, and there will be a risk that the smelting slag will be converted from solid waste to hazardous waste; (2) After the valuable elements in the smelting slag acid leaching liquid are extracted, the residual acid leaching liquid is usually neutralized by lime neutralization. This method can convert the hazardous waste acid leaching liquid into solid waste, but after the lime neutralization of the acid leaching liquid, the total amount of waste slag usually increases a lot, that is, the industrial gypsum with huge output and difficult resource utilization at present. This is because the acid in the smelting slag acid leaching process is usually excessive, and the excess acid needs to be neutralized with corresponding lime, while the content of valuable elements is relatively low, which means that the amount of waste slag in the whole process is increased. How to solve the problems existing in the wet treatment process of smelting slag is a hot spot and difficulty in current research. The present invention is also proposed based on this. Summary of the invention

[0006] The purpose of the present invention is to provide a method for removing impurities from the high-pressure hydrolysis products of cobalt-iron alloy acid leaching solution containing iron solid waste, solve the problem of purification and resource utilization of the high-pressure hydrolysis products of cobalt-iron alloy acid leaching solution, and finally obtain an iron-containing solid waste product with lower impurity quality, providing a valuable iron source for lithium iron phosphate positive electrode materials.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for removing impurities from a high-pressure hydrolysis product of an iron-containing solid waste cobalt-iron alloy acid leaching solution, comprising the following steps:

[0009] S1. Add the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution into the ferric chloride solution, mix and stir, centrifuge, and wash;

[0010] S2, adding the washed solid obtained in S1 to the aqueous ammonia solution, mixing, stirring, and centrifuging;

[0011] S3, the solid obtained by centrifugation in S2 is transferred into a sodium hydroxide solution, fully stirred, and then subjected to a hydrothermal reaction. The obtained product is centrifuged, washed with water, and dried to obtain an iron-containing material product, thus completing the impurity removal treatment.

[0012] Further, in S1, the concentration of the ferric chloride solution is 4-6wt%, and illustratively, it can be 4%, 5% or 6%, etc. The ratio of the added amount of the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution to the ferric chloride solution is 1g: (25-35)mL, and illustratively, it can be 1g: 30mL, etc.

[0013] Furthermore, in S1, the mixing and stirring time is 1-3 hours; and the rotation speed during the centrifugation process is 3000-5000 rpm.

[0014] Further, in S2, the concentration of the aqueous ammonia solution is 1.5-2.5 wt%, and illustratively, it can be 2%;

[0015] The ratio of the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution in S1 to the added amount of the ammonia water is 1g: (15-25)mL, and illustratively, it can be 1g: 20mL.

[0016] Furthermore, in S2, the mixing and stirring time is 0.5 to 1.5 h.

[0017] Furthermore, in S3, the pH value of the system is controlled to be 11-12 during the sufficient stirring process. For example, the pH value may be 11, 12, and so on.

[0018] Furthermore, in S3, the temperature of the hydrothermal reaction is 160-200° C. For example, the temperature may be 180° C.

[0019] Furthermore, in S3, the hydrothermal reaction time is 0.5 to 1.5 h. Exemplarily, the reaction time may be 1 h.

[0020] Furthermore, the mass contents of each element component in the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution are: Al 0.002%, Ca 0.016%, Co 0.027%, Cr 0.005%, Cu 0.072%, Mn 0.066%, Na 0.003%, Pb 0.007%, Ti 0.002%, Zn 1.851%, K 0.009%, and the rest is Fe.

[0021] The prior art generally uses acid leaching to treat nonferrous smelting slag. On the one hand, it consumes a large amount of acid. Nonferrous smelting slag is usually solid waste, but if it is not properly treated after acid leaching, it will become hazardous waste. If the valuable elements in the nonferrous smelting slag are extracted later, a large amount of lime is needed to treat the waste acid. Since the acid used in the process of acid leaching nonferrous smelting slag is usually excessive, it means that the amount of lime used to neutralize the waste acid is large, which will produce a large amount of industrial gypsum. The more prominent problems currently exist are: (1) the content of valuable elements in nonferrous smelting slag is usually low. Although acid leaching has a high efficiency in extracting valuable elements, the cost of acid leaching of nonferrous smelting slag cannot be ignored; (2) the use of lime to neutralize the acid leaching liquid faces the problem of producing a large amount of industrial gypsum. In recent years, the use of industrial gypsum has been limited, resulting in a large amount of gypsum being piled up in enterprises, which has a great impact on both enterprise production and the ecological environment.

[0022] The present invention has found through research that different high-pressure hydrolysis process conditions of iron-containing solid waste cobalt-iron alloy acid leaching solution will also lead to different appearance hues of high-pressure hydrolysis products ( Figure 2), while the iron source of battery-grade iron phosphate requires a very low impurity content (battery-grade anhydrous iron phosphate, main elements (wt%): Fe, 35.7-36.7; P: 20.1-21.1; impurity elements (wt%): Ca, 0.01; Mg, 0.06; Na, 0.02; K, 0.02; Cu, 0.003; Zn, 0.015; Al, 0.05; Mn, 0.1; Ti, 0.18), which is an impurity requirement index that cannot be met by the high-pressure hydrolysis product of the existing iron-containing solid waste cobalt-iron alloy acid leaching solution. Therefore, if the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution is not acid-dissolved, the iron source material that can be used as battery-grade iron phosphate has a high technical threshold. The concept of the present invention is to first mix the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution containing iron-containing waste solids with a ferric chloride solution. The high-pressure hydrolysis product is mainly iron oxide, but also contains a small amount of other metal oxides or compounds (impurities such as CaSO4, PbO, MnO and ZnO). The solubility product of iron oxide is very small. Ferric chloride will react with impurities such as PbO and ZnO (3PbO+2FeCl3=Fe2O3↓+3PbCl2; 3ZnO+2FeCl3=Fe2O3↓+3ZnCl2; 3MnO+2FeCl3=3MnCl2+Fe2O3↓), so that most of the impurity elements Pb, Mn and Zn elements enter the solution. The generated Fe2O3 will not only not introduce new impurities into the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution, but also further increase the iron content of the iron-containing waste solids. The high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution is treated with ferric chloride solution and then treated with ammonia solution. Due to the strong complexing ability of ammonia, it can accelerate the reaction of CaSO4 (CaSO4=Ca 2+ +SO4 2- ) solubility, reducing the content of CaSO4 in the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution, thereby reducing the content of calcium in the iron-containing waste solid. The high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution is treated with an ammonia solution and then hydrothermally treated with a sodium hydroxide solution. Since ZnO is amphoteric, the residual ZnO in the iron-containing waste solid will react with the sodium hydroxide solution to form a water-soluble compound, while the main component Fe2O3 in the iron-containing waste solid does not react with the sodium hydroxide solution, thereby achieving effective impurity removal of the iron-containing waste solid. The high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution is treated with three process processes of ferric chloride solution, ammonia solution and hydrothermal method, and the precipitate is filtered, washed and dried, and has potential application prospects as a battery-grade iron phosphate FePO4 iron source.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) Using the high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution as raw material, through the ferric chloride-ammonia-hydrothermal process and the regulation of reaction conditions and parameters, the impurity elements in the iron-containing waste solid enter the solution to achieve an ingenious method of removing impurities. There are no related technical reports;

[0025] (2) removing impurity elements such as lead and zinc by controlling the reaction conditions of the ferric chloride solution, increasing the solubility of calcium sulfate in the iron-containing waste solid through the ammonia complexation process, achieving the removal of calcium elements, and utilizing the amphoteric characteristics of zinc elements to make them enter the solution through a hydrothermal method, thereby reducing the zinc content in the iron-containing waste solid;

[0026] (3) The method of the present invention is applicable to the purification process of most iron-containing waste solids. The technical method is simple and effective. During the whole process, a large amount of acid is not required to dissolve the iron-containing waste solids and the subsequent use of lime to neutralize the acid leaching solution to form a large amount of industrial gypsum. The obtained iron-containing material has a low impurity content and a high content of the main component Fe2O3. It is suitable as an iron source for battery-grade iron phosphate. The whole reaction process is simple and has the advantages of low impurity removal cost and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a process flow chart of the present invention;

[0028] Figure 2 This is an optical photograph of a powder sample of a high-pressure hydrolysis product of an iron-containing waste solid cobalt-iron alloy acid leaching solution. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0030] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0031] Embodiment 1:

[0032] This embodiment provides a method for removing impurities from the high-pressure hydrolysis product of iron-containing solid waste cobalt-iron alloy acid leaching liquid, and its preparation process is as follows: Figure 1 shown.

[0033] The high pressure hydrolysis product of cobalt-iron alloy acid leaching solution is a yellow or red powder sample, and its optical photograph is as follows Figure 2 As shown. The high-pressure hydrolysis product is mainly derived from the cobalt-iron slag in the copper smelting process, which is enriched by reduction roasting-crushing-magnetic separation, and then obtained by dilute sulfuric acid acid leaching, high-pressure hydrolysis, separation and drying. The composition analysis of the high-pressure hydrolysis product used in this embodiment is shown in Table 1. It can be seen from Table 1 that the content of lead (Pb% = 0.007), zinc (Zn% = 1.851), and calcium (Ca% = 0.016) in the high-pressure hydrolysis product is relatively high. Therefore, it is necessary to remove the lead, zinc and calcium elements in the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution.

[0034] Table 1

[0035]

[0036] In this embodiment, 1 g of high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution was measured, 30 mL of 5 wt% ferric chloride solution was added, and after mixing and stirring for 2 hours, the obtained mixture was centrifuged at 4000 rpm, and the solid matter after centrifugation was washed once with deionized water; the solid matter after centrifugation was added to 20 mL of 3 wt% ammonia solution, mixed and stirred for 1 hour, and then centrifuged at 4000 rpm to obtain a solid matter; the obtained solid matter was added to 50 mL of sodium hydroxide solution, the pH value of the solution was controlled at 11.0, and after sufficient stirring, the mixture was hydrothermally reacted at 180° C. for 1 hour, and then the mixture was centrifuged, washed with water and dried, and the obtained precipitate was the iron-containing material product after impurities were removed.

[0037] The inductively coupled plasma emission spectroscopy (ICP) analysis of the iron-containing material product after impurity removal is shown in Table 2. As can be seen from Table 2, the manganese element is reduced from the original 0.066 (wt%) to undetectable, indicating that the method can effectively remove the manganese element in the iron-containing waste solid; the lead element is reduced from the original 0.007 (wt%) to 0.002 (wt%); sodium (0.003, wt%), potassium (0.009, wt%) and titanium (0.002, wt%) are also reduced to undetectable, indicating that sodium, potassium and titanium also enter the solution during the impurity removal process and are effectively separated from the solid iron-containing material; zinc element is reduced from the original 1.851 (wt%) to 1.166 (wt%), and zinc element is also effectively removed; calcium element is reduced from the original 0.016 (wt%) to 0.007% (wt%).

[0038] Table 2

[0039]

[0040] Embodiment 2:

[0041] In this embodiment, 1 g of high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution was measured, and the composition of each element component was shown in Table 1. Then, it was mixed with 30 mL of 5wt% ferric chloride solution, and after being fully stirred for 2 hours, the obtained mixture was centrifuged at 4000 rpm, and the solid matter after centrifugation was washed once with deionized water; the solid matter after centrifugation was mixed with 20 mL of 3wt% ammonia solution and stirred for 1 hour, and then centrifuged at 4000 rpm to obtain a solid matter; the obtained solid matter was added with 50 mL of sodium hydroxide solution, and the pH value of the solution was controlled at 12.0. After being fully stirred, the mixture was transferred to a hydrothermal reactor, and then hydrothermally treated at 180°C for 1 hour. After the hydrothermal reaction was completed, the mixture was centrifuged, washed with water and dried, and the obtained precipitate was the iron-containing material product after impurities were removed.

[0042] The analysis of the iron-containing material product after impurity removal is shown in Table 3. As can be seen from Table 3, compared with the solution pH value of 11.0, when the solution pH is higher than 12.0, the lead and calcium elements in the iron-containing material are basically unchanged. However, at a higher solution pH value, the zinc element is reduced from the original 1.851 (wt%) to 1.087 (wt%), and the zinc element is further removed. Therefore, the present invention removes impurities from the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution containing iron-containing solid waste to obtain an iron-containing material product with lower impurity quality, which has important application prospects in the field of resource utilization of iron-containing waste solids such as the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution.

[0043] Table 3

[0044]

[0045] The above-mentioned Examples 1 and 2 still contain impurities such as Zn, Al, Co, Cr, and Cu. Although the removal rate is not particularly high compared to the initial raw material ratio, it is very critical for the subsequent preparation of battery-grade iron phosphate:

[0046] (1) The high-pressure hydrolysis product is a product obtained under an acidic (sulfuric acid) environment, and is relatively acid-resistant and stable. After being hydrothermally treated with ferric chloride, ammonia water and sodium hydroxide solution, the high-pressure hydrolysis product is in an activated state, and the surface that was originally very acid-resistant is activated (the surface of the high-pressure hydrolysis product was originally acidic, and now it is adjusted to an alkaline surface, which is easy to react with phosphoric acid) and is used for subsequent reaction with phosphoric acid to prepare battery-grade iron phosphate. Since phosphoric acid is a medium-strength acid and its acidity is not as strong as sulfuric acid, and the high-pressure hydrolysis product is obtained under strong acidic conditions, if it is not treated by the method of the present invention, the high-pressure hydrolysis product is difficult to react with phosphoric acid, and it is difficult to prepare iron phosphate.

[0047] (2) Anhydrous battery-grade iron phosphate has no limit on the content of Co and Cr. The Al content in the high-pressure hydrolysis product (0.002, wt%) is lower than the required standard for battery-grade iron phosphate (0.05, wt%). These three elements do not have much impact. The Cu content (0.072, wt%) in the high-pressure hydrolysis product is somewhat reduced after impurity removal (0.066, wt%). Although the reduction is not much, it is very important for the subsequent preparation process of iron phosphate. After being treated with ammonia water, the Cu in the high-pressure hydrolysis product will form copper ammonia complex ions with ammonia water (due to the high-pressure hydrolysis process, the copper element is embedded in the iron oxide. Although the copper ammonia complex ions soluble in water are formed at this time, they cannot enter the solution). After being treated with sodium hydroxide solution, the alkaline complex form of copper is formed. When reacting with phosphoric acid, the phosphoric acid will react with the hydroxide ions in the alkaline complex of copper, so that the copper element returns to the form of copper ammonia complex ions. At this time, the phosphoric acid has reacted with the main component of the high-pressure hydrolysis product, iron oxide, so that the copper ammonia complex ions originally embedded in the iron oxide enter the solution, thereby achieving separation. The Zn element also has a similar process to Cu. The content of zinc in the high-pressure hydrolysis product is about 1.851wt%, and the zinc content after impurity removal is 1.087wt%. The reduction of zinc content is also due to the fact that zinc has amphoteric properties. Under strong alkaline conditions, it forms water-soluble sodium zincate, which reduces the zinc content from 1.851wt% to 1.087wt%. However, a large part of zinc is embedded in iron oxide (the main component of high-pressure hydrolysis product), and iron oxide and sodium hydroxide do not react. Therefore, the zinc embedded in the iron oxide main body cannot be removed, but the zinc embedded in the iron oxide main body can form zinc ammonia complex ions with ammonia water. Although it is still embedded in the iron oxide main body at this time, it will subsequently react with phosphoric acid. When phosphoric acid destroys the iron oxide main body, the zinc element can be separated from the main body and enter the solution, so it is also easy to separate. Therefore, the high-pressure hydrolysis product treated by the technical method of the present invention has more application prospects.

[0048] Comparative Example 1:

[0049] Compared with Example 1, most of the steps are the same except that the addition of ferric chloride solution is omitted, that is, the high-pressure hydrolysis product of the cobalt-iron alloy acid leaching solution is directly mixed with the ammonia solution and the NaOH solution in sequence.

[0050] 1g of high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution was added to 20mL of 3wt% ammonia solution, mixed and stirred for 1h, and then centrifuged at 4000rpm to obtain solids, and then the obtained solids were added to 50mL of sodium hydroxide solution, the pH value of the solution was controlled at 11.0, and after sufficient stirring, the mixture was hydrothermally reacted at 180℃ for 1h, and the mixture was centrifuged, washed and dried. The obtained precipitate was subjected to ICP analysis, as shown in Table 4. As can be seen from Table 4, the manganese element has changed from the original 0.066wt% to 0.065%wt%, which is basically not much different; the lead element content has not changed much either. The zinc element content has decreased slightly, from 1.851wt% to 1.573wt%. The decrease in zinc element content is mainly due to the reaction of alkaline sodium hydroxide solution with zinc oxide to form sodium zincate. This indicates that ferric chloride solution is relatively effective in removing manganese, lead and zinc elements (3PbO+2FeCl3=Fe2O3↓+3PbCl2; 3ZnO+2FeCl3=Fe2O3↓+3ZnCl2; 3MnO+2FeCl3=3MnCl2+Fe2O3↓), and plays an important role in the subsequent removal of impurities from the high-pressure hydrolysis product and its reaction with phosphoric acid to prepare iron phosphate.

[0051] Table 4

[0052]

[0053] Comparative Example 2:

[0054] Compared with Example 1, most of them are the same, except that the step of treating with aqueous ammonia solution is omitted, that is, the solid matter treated with ferric chloride solution is directly added to the sodium hydroxide solution.

[0055] 1g of high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution was measured, and 30mL of 5wt% ferric chloride solution was added. After mixing and stirring for 2h, the obtained mixture was centrifuged at 4000rpm, and the solid matter after centrifugation was washed once with deionized water. The obtained solid matter was mixed and stirred with 50mL of sodium hydroxide solution, and the pH value of the solution was controlled at 11.0. After sufficient stirring, the mixture was hydrothermally reacted at 180℃ for 1h. After the reaction was completed, the mixture was centrifuged, washed with water and dried. The obtained precipitate was subjected to ICP analysis, as shown in Table 5. As can be seen from Table 5, without adding ammonia water treatment, the zinc content in the high-pressure hydrolysis product after impurity removal was reduced from the original 1.851wt% to 1.413wt%, and the copper content was reduced from the original 0.072wt% to 0.071wt%, and the copper content did not change much. Since copper and zinc elements easily form water-soluble copper ammine ions and zinc ammine ions with ammonia water, if the high-pressure hydrolysis product is not treated with ammonia water, the copper and zinc impurities embedded in the iron oxide (the main component of the high-pressure hydrolysis product) are not easy to remove in the subsequent process. Therefore, it is more important to treat the high-pressure hydrolysis product with ammonia water.

[0056] Table 5

[0057]

[0058] Comparative Example 3:

[0059] Compared with Example 1, most of them are the same, except that the amount and concentration of the sodium hydroxide solution are adjusted and the pH value of the system is controlled to be 13 (reflecting that the pH must be 11-12).

[0060] 1g of high-pressure hydrolysis product of cobalt-iron alloy acid leaching solution was measured, and 30mL of 5wt% ferric chloride solution was added. After mixing and stirring for 2h, the obtained mixture was centrifuged at 4000rpm, and the solid after centrifugation was washed once with deionized water; the solid after centrifugation was added to 20mL of 3wt% ammonia solution, mixed and stirred for 1h, and then centrifuged at 4000rpm to obtain a solid; the obtained solid was added to 50mL of sodium hydroxide solution, and the pH value of the solution was controlled at 13.0. After sufficient stirring, the mixture was hydrothermally reacted at 180℃ for 1h, and then the mixture was centrifuged, washed with water and dried. The obtained precipitate was the iron-containing material product after impurity removal, which was analyzed by ICP, as shown in Table 6. As can be seen from Table 6, further increasing the pH to 13.0 further reduces the aluminum and zinc elements in the high-pressure hydrolysis product after impurity removal, but the effect is not very obvious. Compared with pH 12.0, the zinc content only decreased from 1.087wt% (pH=12.0) to 1.083wt% (pH=13.0), and the aluminum content only decreased from 0.00144wt% (pH=12.0) to 0.0012wt% (pH=13.0). However, at pH=13.0, a sodium ion content of 0.015wt% was detected, while it was not detected at pH=12.0. At pH=13.0, the sodium ion content of 0.015wt% was close to the sodium ion content of 0.02wt% required by standard ferric phosphate, indicating that further increasing the pH value will increase the alkalinity of the solution. Although it will further reduce the aluminum and zinc contents (the effect is not obvious), the hydroxide ions in the strong alkaline solution will further corrode the high-pressure hydrolysis product. Although the aluminum and zinc inside the high-pressure hydrolysis product are released, the corroded holes will cause the sodium ions to remain inside, increasing the difficulty of water washing. Therefore, an increase in pH will increase the release of zinc and aluminum in the high-pressure hydrolysis products of the cobalt-iron alloy acid leaching solution, but a higher alkaline solution system will lead to the residue of sodium ions, which is not conducive to the subsequent preparation of iron phosphate. This is because battery-grade iron phosphate will form a colloidal precursor during the preparation process, and the colloidal precursor has a strong adsorption capacity for sodium ions, making it difficult to wash and remove the sodium ions.

[0061] Table 6

[0062]

[0063] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for removing impurities from high-pressure hydrolysis products of iron-containing solid waste cobalt-iron alloy acid leaching solution, characterized in that: The following steps are involved: S1. Add the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution into the ferric chloride solution, mix and stir, centrifuge, and wash; S2, adding the washed solid obtained in S1 to the aqueous ammonia solution, mixing, stirring, and centrifuging; S3, the solid obtained by centrifugation in S2 is transferred into a sodium hydroxide solution, fully stirred, and then subjected to a hydrothermal reaction. The obtained product is centrifuged, washed with water, and dried to obtain an iron-containing material product, thus completing the impurity removal treatment.

2. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: The concentration of the ferric chloride solution is 4-6wt%, and the ratio of the added amount of the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching liquid to the ferric chloride solution is 1g: (25-35)mL.

3. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S1, the mixing and stirring time is 1-3 hours; the rotation speed during the centrifugation process is 3000-5000 rpm.

4. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S2, the concentration of the ammonia solution is 1.5-2.5 wt%; The ratio of the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution in S1 to the added amount of the ammonia water is 1g: (15-25)mL.

5. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S2, the mixing and stirring time is 0.5 to 1.5 h.

6. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S3, the pH value of the system is controlled to be 11-12 during the sufficient stirring process.

7. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S3, the temperature of the hydrothermal reaction is 160 to 200°C.

8. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 7, characterized in that: In S3, the temperature of the hydrothermal reaction is 180°C.

9. The method for removing impurities from the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution according to claim 1, characterized in that: In S3, the hydrothermal reaction time is 0.5 to 1.5 h.

10. The method for removing impurities from high-pressure hydrolysis products of iron-containing solid waste cobalt-iron alloy acid leaching liquid according to claim 1, characterized in that: The mass contents of the various element components in the high-pressure hydrolysis product of the iron-containing solid waste cobalt-iron alloy acid leaching solution are: Al 0.002%, Ca 0.016%, Co 0.027%, Cr 0.005%, Cu 0.072%, Mn 0.066%, Na 0.003%, Pb 0.007%, Ti 0.002%, Zn 1.851%, K 0.009%, and the rest is Fe.

Citation Information

Patent Citations

  • Method for extracting and separating valuable metals from high leaching slag produced by hydrometallurgy

    CN104722410B

  • Method for comprehensively recovering valuable metal from zinc smelting slag

    CN109402411A